2004
DOI: 10.1002/cncr.20338
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of celecoxib and infusional 5‐fluorouracil as second‐line treatment for advanced pancreatic carcinoma

Abstract: BACKGROUND Cyclooxygenase‐2 (COX‐2) is up‐regulated frequently and may constitute a promising therapeutic target in patients with pancreatic ductal adenocarcinoma (PDAC). METHODS Patients with advanced PDAC who had progressive disease after gemcitabine‐based chemotherapy were eligible for this pilot study. Treatment was comprised of oral celecoxib (400 mg twice daily) and protracted intravenous (i.v.) infusion 5‐fluorouracil (5‐FU) (200 mg/m2 per day), both given continuously for a maximum of 9 treatment month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(50 citation statements)
references
References 32 publications
5
45
0
Order By: Relevance
“…In a clinical trial, the patients with advanced pancreatic adenocarcinoma were given celecoxib in combination with 5-fluorouracil. The results showed that celecoxib with 5-fluorouracil was capable of inducing durable and objective responses, even in gemcitabine-resistant pancreatic cancer (Milella et al, 2004). These results collectively suggest that COX-2 inhibition with other novel agents could be useful in future clinical trials for pancreatic cancer.…”
Section: Targeting Cox-2 For Enhancing Cancer Therapeutic Efficacymentioning
confidence: 78%
“…In a clinical trial, the patients with advanced pancreatic adenocarcinoma were given celecoxib in combination with 5-fluorouracil. The results showed that celecoxib with 5-fluorouracil was capable of inducing durable and objective responses, even in gemcitabine-resistant pancreatic cancer (Milella et al, 2004). These results collectively suggest that COX-2 inhibition with other novel agents could be useful in future clinical trials for pancreatic cancer.…”
Section: Targeting Cox-2 For Enhancing Cancer Therapeutic Efficacymentioning
confidence: 78%
“…Finally, evidence from several experimental and clinical studies has shown that selective Cox-2 inhibitors possess significant antitumor activity on their own with favorable safety profile (1,8,21,22,48) and can also enhance tumor response to radiation or cytotoxic agents (49,50). However, recent clinical studies (51,52) with rofecoxib in the treatment of metastatic colorectal cancer pointed out an increased toxicity and lack of efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, COX-2 inhibitors have also gained attention, either alone or in combination with other chemotherapeutic agents and/or radiation therapy, in the treatment of cancer (1). For example, a COX-2-selective inhibitor celecoxib exerted synergistic antitumor effects when combined with gemcitaine or 5-fluorouracil in patients with advanced pancreatic cancer (2), and it enhanced the response to paclitaxel and carboplatin in early-stage non -small cell lung cancer (3). The mechanism underlying the antitumor activity of COX-2 inhibitors is thought to involve inhibition of COX-2 enzyme activity and induction of apoptosis, but it is unclear whether COX-2 inhibition is required to induce apoptosis (4).…”
Section: Introductionmentioning
confidence: 99%